Efektivitas Monitoring Glukosa Darah dengan Pengambilan Sampel di Telapak Tangan Terhadap Penurunan Nyeri Akibat Tusukan Jarum pada Pasien Diabetes Mellitus - Laili Fitriana; Agung Waluyo; Lestari Sukmarini (Journal of Telenursing (JOTING), 2023)
This literature study aims to determine Effectiveness of Blood Glucose Monitoring by Sampling on the Palm of the Hand in Reducing Needlestick Pain in Diabetes Mellitus Patients. The research design is a systematic review, using 6 databases, ProQuest, EMBASE, SpringerLink, Sage Journals, Scopus and Taylor and Francis. A total of 10 articles were reviewed from 2010 to 2022. The keywords used in the literature search were Diabetes Mellitus AND Blood Glucose AND pain AND palm site AND fingertip. The protocol and literature review evaluation used the Critical Appraisal Skills Program issued by the JBI Guideline. The results of the study showed that the palms of the hands as blood glucose sampling sites were effective in reducing pain due to needle pricks in patients with diabetes mellitus. In addition, pain can also be minimized by adjusting the diameter of the lancet and the depth of the puncture and using the latest technology/method for testing blood glucose. In conclusion, palms as an alternative site for blood glucose sampling are effective in reducing pain due to needle pricks in patients with diabetes mellitus. Keywords: Diabetes Mellitus, Blood Glucose, Pain, Palms, Fingertips